Estimating the size of Turkey's informal sector: an expenditure-based approach - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2008)
Accurately measuring Turkey's informal sector is important for policymaking. We utilize household income-expenditure surveys to examine this sector's income underreporting. The Pissarides-Weber approach hypothesizes that data would reflect such underreporting as excess food consumption. Our results suggest informal sector members spend more than their formal sector counterparts with comparable reported income levels. Using this information, we estimate the average size of the true informal sector to be about 1.25 times the official estimate. The informal sector accounts for around 83% of officially reported disposable income. Therefore, true Turkish disposable income is (25%)*(83%), roughly 21% larger than the officially estimated magnitude.
Keywords: informal economy; tax evasion; Engel's Law